A distributed energy management scheme with the extended optimization horizon for Energy Internet. (September 2022) - Cheng, Yijun; Peng, Jun; Liu, Kaiyang; Jiang, Fu; Wu, Yue; Huang, Zhiwu
Abstract: This paper proposes a distributed energy management with the extended optimization horizon for Energy Internet to minimize the system operation cost. The scheme dispatches various of controllable distributed energy sources of the traditional energy generation and battery energy storage devices. Two original contributions make the proposed scheme distinctive from the existing studies. Firstly, both the classical alternating direction method of multipliers (ADMM) and symmetric ADMM are combined in the new scheme to acquire fast and stable energy management policy, which improves the efficiency of energy management decisions. Secondly, an extended optimization horizon is designed based on the data from the previous day to simultaneously minimize the long-term cost and maintain battery state-of-charge. Simulation results from Pecan Street dataset demonstrate the superiority of the proposed method. Compared to existing distributed methods, the convergence time is reduced by almost 80% and the long-term cost is reduced by 47.8%. Highlights: A distributed energy management scheme is proposed for Energy Internet. A hybrid ADMM is proposed for a fast and stable energy management policy. An extended optimization horizon is designed to minimize the long-term cost. The efficiency of the proposed scheme is verified through Pecan Street dataset.